PENGEMBANGAN MEDIA MIND MAPPING DIGITAL UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK ANAK USIA 5-6 TAHUN - Syarifah Aini; Febrialismanto Febrialismanto; Daviq Chairilsyah (Program Studi Pendidikan Guru PAUD Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
This study was conducted to achieve the targets of finding out the readiness and benefits obtained from the improvement of digital mind mapping media to increase their expertise in pursuing children aged 5-6 years. An R&D (Research and Development) study is a study conducted, and the stages carried out in this R&D study are: abilities and problems, collecting data, project sketches, validating sketches, testing research locations, improving sketches, and creating projects. The method used in collecting information carried out in this study was using instrument sheets and documentation. Validation of the feasibility of media instruments and validation of material products are two types of validation used. The child assessment instrument sheet can be used for limited field tests. The quantitative descriptive analysis technique used in this study is a way of analyzing the information used in this study. Based on the conclusion of the study based on the validation obtained from 7 (seven) validations, it can be deduced in the